The Dualism of Deindustrialisation and Innovation - Piotr WALĄG; Maciej GLINIAK (Communications of International Proceedings, 2020)
The issue of structural changes from the point of view of shaping and, at the same time, achieving sustainable economic growth through effective management of production factors (effective allocation) is a key area of research into changes in the structure of the economy as such. Sustainable growth is defined as sustainable economic growth at full employment, resilient to shocks and crises in the economy as well as to the shocks in demand and, for catching up countries, eliminates the risk of falling into the medium growth trap. The aim of this work is to examine whether the dualism of the deindustrialisation process in the Polish economy between 1995 and 2018 was determined by the level of innovation in the industrial sector. How and whether the presence of this phenomenon in the economy may be an appropriate criterion for assessing the level of innovation in the industrial sector in the context of long-term sustainable economic growth. There is also a hypothesis that in the Polish economy, the key determinant of dualism in the deindustrialisation process, and/or the main reason for the trap of average growth, was the lack of innovation in the processing industry sector. Despite the fact that the growing demand in the Polish economy, and above all GDP per capita, was the most decisive factor determining the share of manufacturing in total employment, and thus its production, causing the largest increase in its share in total production in the whole analysed period 1995-2018. It was the very low level of innovation in the manufacturing sector that caused the decrease in its share in total employment, being the main reason for the emergence of the phenomenon of dualism in the deindustrialisation process, which was a brake on sustainable economic growth and resulted in the economy being stuck in the trap of average growth.
Keywords: deindustrialisation; sustainable economic growth; dualism of the deindustrialisation process; average growth trap; criterion for assessing the level of innovation.